Developing skills for employability with German Partners : 8 success stories from Sub-Saharan Africa - Niediek, Silvia [Verfasser] (Bundesinstitut für Berufsbildung, 2014)
Each of the 'Developing Skills for Employability with German Partners' brochures presents eight vocational education and training success stories of German and international partners in various countries and regions. These brochure presents eight success stories of skill development realised in a joint effort by partners from Germany and Sub-Saharan Africa. With its wide range of training offers and its strong emphasis on employability, 'Training - Made in Germany' has the potential to successfully contribute to the design process of the training systems in Africa through African-German cooperation projects." (BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; I 2.3.1 Afrika; Berufsbildung; Internationale Zusammenarbeit; Bundesrepublik Deutschland; Afrika; Subsahara-Afrika